Sports Comparison of Running Speed of Blind Athletes Using Technology Assistance and Guide Runner - Ghalib, Najwan Muhammad; Rafly Ikhsanudin Al Afghani; Dadan Hamdalah Kahfi; Reka Septiany; Bilal Insan Tawakal; Suherman Slamet; Gano Sumarno; Mesa Rahmi Stephani (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
The purpose of this paper is to compare the running speed of blind athletic athletes at NPCI Bandung City by disclosing the difference in running speed performance of blind athletic athletes in Bandung City when using a running method assisted by a guide runner and when using technological innovations created by students and a lecturer at the Indonesian University of Education, namely Blind Run. This technological innovation received an award from KEMENPORA of the Republic of Indonesia in 2022 and has been implemented for blind athletic athletes at the Bandung City NPCI. The sampling technique used by the researcher is purposive sampling, namely, athletes who are blind and have adapted to using the Blind Run product. A quantitative research method with the Mann-Whitney test is applied to answer the research hypothesis. The researchers' findings showed that athletes who ran using different methods had insignificant differences in speed. This is evidenced by the comparative test results, namely the sig. (2-tailed) of 0,121 or > 0,05 so that hypothesis can be terminated.